Negotiating The Social Relationships Through The Discourse of Social Networking Sites (SNSs) Commenting on West Java Paragliding World Championship (WJPWC) 2019 - Suroto Suroto; Ika Yatmikasari (CALL, 2020)
The Research analyzes how the social relationships are negotiated through the discourse of social networking sites in the form of Facebook status commenting on West Java Paragliding World Championship (WJPWC) 2019. The analysis focuses on how the participant tells her feelings about things and people through her Facebook status during the WJPWC event. By the qualitative descriptive method, the Facebook status of a paragliding legend was analyzed using the interpersonal metafunction of Halliday’s Systemic Functional Linguistics and appraisal theory of Martin and Rose. Using the interpersonal metafunction, the attitudes and judgments of the participant are evaluated based on the speech roles, mood types, and modalities used in the text. The appraisal theory is used for further evaluation to know how the feelings of the participant by evaluating (1) the kinds of attitudes (affect, judgment and appreciation), (2) the attitude resources, and  (3) how the attitudes are amplified. The result showed that the participant through her four Facebook status consisted of 26 clauses used the speech roles of giving information in the mood types of declarative. By the mood types, the participant directly and explicitly showed the positive attitudes commenting on the WJPWC event and realized in several linguistic realizations. The participant who roles as the attitude resources expressed her feelings in three main types of attitudes; (1) her positive affect or feelings, (2) her positive judgment of personal and moral, and (3) her positive and negative appreciation of valuing thing during the WJPWC event. The participant also used several metaphors that play important roles in constructing her gradable feelings and emotion.Keywords: Appraisal Theory, Attitude Evaluation, Interpersonal metafunction,                   Systemic Functional Linguistics